PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN POWER POINT DAN AUDIOVISUAL TERHADAP HASIL BELAJAR IPSEKONOMI SISWA KELAS VII SMPN 6 SIAK HULU KABUPATEN KAMPAR - Zelfiani, Winda Okta; Indrawati, Henny; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The learning result is the ability of the student after he received alearning experience, to determine the results of the study carried out using the test.Basically, student learning outcomes in social studies Economics at SMPN 6 Siak HuluKampar regency still low. This happens because teachers often use the conventionalmethod of learning which is still dominated by lectures so monotonous, and the lack ofuse of media subjects during teaching and learning process. Given this research, aimsto determine the effect of the use of instructional media and audiovisual power pointtowards learning outcomes IPS Economy class VII SMPN 6 Siak Hulu Kampar regency.This study uses primary data and secondary data. The population in this study were allstudents or a student of class VII SMPN 6 Siak Hulu Kampar numbered 80 students.samples taken in this study 54 students appointed intentionally (purposive). This studyshows that in general learning media in the form of power point, pictures and videossignificant effect by 19%.Keywords: Learning Media Power Point and Audiovisual, Learning Outcomes